Tunability of Electronic Properties and Magnetic Behaviour of Nickel Oxide: A Review - Acharya, Aman D.; Sarwan, Bhawna (Current Nanoscience, 2019)
Background: Significant efforts in direction of development of smart windows with natural colour switching properties, which are in the current interest. The tailoring of the electrical conductivity as n-type and p-type is still a major challenge. In this regard, NiO has emerged as a potential candidate and auspicious functional material for various applications. Objective: The main objective is to compile the interesting findings of the authors in context to the effect of the different filler on the properties especially electric and magnetic of NiO on one platform. Methods: Literature survey has been done in the depth. As a whole near about 192 Research articles which include oldest as well as recent coverage about the NiO. Conclusions: Review report conclude that instead of Mott insulator NiO is a kind of charge transfer insulator and accepted extensively theoretically as well as experimentally.
Keywords: dilute magnetic semiconductor